Polyvinyl alcohol film and optical film produced from the same
Patent Information
- Application Number
- JP2023133669
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-06
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-17
AI Technical Summary
Existing polyvinyl alcohol films used in optical films, particularly polarizing films, experience a significant decrease in the degree of polarization over long-term use due to factors such as high temperature and humidity.
The polyvinyl alcohol films are treated with a 4 wt% boric acid solution at 55°C for 1 minute to achieve a specific range of area swelling (17.0 to 38.0%) and an inflection point temperature of storage modulus (E') between 37°C and 40°C, controlling the degree of polarization and shrinkage.
The treated films maintain an excellent degree of polarization (99.99%) with minimal reduction (0.01% or less) after 500 hours at 80°C, and exhibit low shrinkage rates (1% or less) in both directions, preventing warping and maintaining film integrity under high-temperature conditions.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to polyvinyl alcohol (PVA) products, and in particular, but not exclusively, to polyvinyl alcohol films and optical films made therefrom. [Background technology]
[0002] Polyvinyl alcohol (PVA) film is a hydrophilic material obtained by coating and drying an aqueous solution containing polyvinyl alcohol polymer and plasticizer. It has properties such as high transparency, mechanical strength, water solubility, and good processability, and is therefore widely used in packaging materials and various optical films for electronic devices, such as polarizing films.
[0003] The polarizing film obtained by processing the polyvinyl alcohol film through the polarizing process has the property of blocking only light from a specific direction, so that the brightness of the light that passes through can be controlled. Based on this property, the polarizing film is applied to various displays, glasses, and wearable terminals, and has become an indispensable component. The polarizing process generally includes processes such as swelling, stretching, and dyeing, and more specifically, the polyvinyl alcohol film is placed in a solution and the above-mentioned process is carried out to diffuse the dye molecules into the molecules in the polyvinyl alcohol film, and a relatively regular arrangement is obtained by stretching, so that the polarizing film can absorb the light component parallel to the arrangement direction and pass the light component perpendicular to the arrangement direction to produce the property of polarization.
[0004] A polarizing film must have suitable optical properties (e.g., high polarization degree and low polarization degree loss). For this reason, in the prior art, the structure of polyvinyl alcohol is changed or functional groups are added to improve the optical properties. Prior art such as Patent Document 1 provides a polarizing film with excellent polarization performance and low shrinkage stress by simultaneously controlling the total necking ratio (A) during the production of the polarizing film, the necking ratio (B) in the stretching process, and the necking ratio (C) in the drying process. By controlling the total necking ratio (A), it is possible to suppress the decrease in polarization performance and yield, and by appropriately controlling the necking ratio (B) in the stretching process and the necking ratio (C) in the drying process, it is possible to produce a polarizing film with excellent polarization performance and low shrinkage stress.
[0005] Incidentally, the polarizing films disclosed in the prior art such as Patent Document 2 use a dyed cellulose triacetate film as a protective layer in order to suppress a decrease in the polarization degree of the polarizing film under high temperature and high humidity conditions. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Taiwan Patent Publication No. 202231448 [Patent Document 2] Taiwan Patent Publication No. 202212872 Summary of the Invention [Problem to be solved by the invention]
[0007] In the prior art, when an optical film is manufactured using a polyvinyl alcohol film, it is common to find that the polarization degree is significantly reduced after long-term use. In this regard, the present inventors have found that by immersing a polyvinyl alcohol film in a boric acid solution of a specific temperature, time and concentration to have a specific range of surface swelling and to adjust the temperature at which the inflection point of the storage modulus (E') in a specific temperature range is in a specific range, the manufactured polarizing film has an excellent polarization degree, and the problem of the polarization degree reduction of the optical film after long-term use can be improved. [Means for solving the problem]
[0008] Specifically, one aspect of the present invention provides a polyvinyl alcohol film comprising a polyvinyl alcohol resin having a degree of saponification of 95 mol % or more, which has an areal swelling degree of 17.0 to 38.0% obtained when immersed in a 4 wt % aqueous boric acid solution at 55°C for 1 minute, and has an inflection point of storage modulus (E') in water at a temperature range of 30°C to 55°C of 37 to 40°C.
[0009] In one or more embodiments, the polyvinyl alcohol film has an area swelling degree of 17.5 to 35.0% and an inflection point temperature of 37.8 to 38.5°C.
[0010] In one or more embodiments, the polyvinyl alcohol film obtained by immersing in a 4 wt % boric acid solution at 55°C for 1 minute has a swelling degree in the transverse direction (TD) of 9.0 to 18.0% and a swelling degree in the machine direction (MD) of 7.5 to 18.0%.
[0011] In one or a plurality of embodiments, the polyvinyl alcohol film has a swelling degree in the TD direction of 9.0 to 16.50%, and a swelling degree in the MD direction of 8.0 to 16.0%.
[0012] In one or a plurality of embodiments, the absolute value of the difference between the swelling degree in the TD direction and the swelling degree in the MD direction of the polyvinyl alcohol film is 5% or less.
[0013] In one or more embodiments, the ratio of the swelling degree in the TD direction to the swelling degree in the MD direction of the polyvinyl alcohol film is 0.9 to 1.7.
[0014] In one or more embodiments, the ratio of the swelling degree in the TD direction to the swelling degree in the MD direction of the polyvinyl alcohol film is 0.95 to 1.60.
[0015] In one or more embodiments, the polyvinyl alcohol film has an average degree of polymerization of 1,500 to 3,500.
[0016] In one or more embodiments, the polyvinyl alcohol film has an average degree of polymerization of 2,000 to 3,500.
[0017] In one or more embodiments, the polyvinyl alcohol film has a thickness of 30 to 75 μm.
[0018] Another aspect of the present invention provides an optical film made from the polyvinyl alcohol film described above.
[0019] In one or more embodiments, the optical film is a polarizing film.
[0020] In one or more embodiments, the polarization degree of the polarizing film is 99.99% or more.
[0021] In one or more embodiments, when the polarizing film is heat-treated at 80° C. for 500 hours, the decrease in the degree of polarization is 0.01% or less.
[0022] In one or more embodiments, the polarizing film is heat-treated at 80° C. for 500 hours, and the area shrinkage rate is 2% or less.
[0023] In one or more embodiments, when the polarizing film is heat-treated at 80° C. for 500 hours, the shrinkage rate in the TD direction and the shrinkage rate in the MD direction are both 1% or less. Effect of the Invention
[0024] The polyvinyl alcohol film of the present invention can be used for various purposes, but is particularly suitable for producing optical films such as polarizing films. The polarizing film produced using the polyvinyl alcohol film obtained by the technical content of the present invention has an excellent polarization degree and can improve the deterioration of the polarization degree after long-term use.
[0025] In addition, the inventors have found that when the polyvinyl alcohol film of the present invention is immersed in a boric acid solution of a specific temperature, time and concentration, and controlled to have a swelling degree in a specific range, an optical film with improved shrinkage can be produced, and when the polyvinyl alcohol film has a TD swelling degree and a MD swelling degree in a specific range, the optical film produced by the polyvinyl alcohol film has an improved shrinkage rate in the corresponding direction.Therefore, the present invention can prevent the warping of the corners of the optical film caused by long-term use under high temperature environment. [Brief description of the drawings]
[0026] [Figure 1] 1 is a graph showing the storage modulus (E') of a polyvinyl alcohol film according to a change in temperature analyzed in water in accordance with an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating a sample preparation method for analyzing the inflection point temperature of a polyvinyl alcohol film according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram illustrating a sample preparation method for analyzing the inflection point temperature of a polyvinyl alcohol film according to one embodiment of the present invention. [Figure 4]FIG. 2 is a schematic diagram illustrating a sample preparation method for analyzing the inflection point temperature of a polyvinyl alcohol film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] In order to make the description of the present invention more detailed and complete, the following provides an illustrative description of the embodiments and specific examples of the present invention, which are not the only ways of implementing or operating the specific examples of the present invention. In this specification and the appended claims, "a" and "the" may also be interpreted as plural unless the context dictates otherwise.
[0028] The numerical ranges and parameters specifying the present invention are approximate, but the relevant numerical values in the specific examples are presented as precisely as possible. However, any numerical value necessarily contains standard deviations inherent in each individual testing method. As used herein, the term "about" indicates that the actual value is within an acceptable standard error of the mean and is within the belief of one of ordinary skill in the art to which the present invention pertains.
[0029] [Polyvinyl alcohol film] One aspect of the present invention provides a polyvinyl alcohol film that contains a polyvinyl alcohol resin with a degree of saponification of 95 mol% or more, has an areal swelling degree of 17.0 to 38.0% obtained by immersion in a 4 wt% aqueous solution of boric acid at 55°C for 1 minute, and has an inflection point of storage modulus (E') in water at a temperature range of 30°C to 55°C of 37 to 40°C. According to some embodiments, the thickness of the polyvinyl alcohol film of the present invention is 30 to 75 μm. Specifically, the thickness is a value within a range between any two of the following values, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, and 75 μm, and the above values are merely examples and are not limiting.
[0030] The "swelling degree" mentioned in this specification includes the "area swelling degree", the "transverse direction swelling degree (hereinafter referred to as the TD swelling degree)" and the "machine direction swelling degree (hereinafter referred to as the MD swelling degree)" of the polyvinyl alcohol film. The "area swelling degree obtained by immersing in a 4 wt% boric acid solution at 55°C for 1 minute (hereinafter referred to as the area swelling degree)" mentioned in this specification is obtained by immersing a polyvinyl alcohol film in a 4 wt% boric acid solution at 55°C for 1 minute and then calculating the area change of the polyvinyl alcohol film.
[0031] The polyvinyl alcohol film has a crystalline region and an amorphous region. When the polyvinyl alcohol film is immersed in a boric acid solution, the aqueous solution containing boric acid penetrates into the amorphous region of the film, dissolving some of the crystals, and the boric acid in the solution also crosslinks the molecules. The inventors have found that the numerical range of the area swelling degree is related to the polarization degree, polarization degree reduction state, and shrinkage rate of the optical film produced thereafter. Presumably, when more crystals are dissolved, the number of bonds with boric acid increases, and the intermolecular structure becomes more stable. It is believed that when the crystalline portion is dissolved, the chain segments at the dissolved site are arranged in a relatively orderly manner, and can move freely to change the distance between the chain segments, so that more positions suitable for boric acid bonds can be generated. The chain segments that are themselves amorphous have an indefinite spacing and a disordered arrangement, so there are fewer positions to bond with boric acid. Thus, if the swelling degree of the polyvinyl alcohol film is too low, the dissolved crystals are reduced, and the number and area of chain segments that can be crosslinked with boric acid are also reduced, resulting in an unstable intermolecular structure, which is easily changed by heat, leading to a decrease in the polarization degree of the optical film thereafter, and also to an in-plane shrinkage that makes the polarizing film more likely to be deformed. On the other hand, if the swelling degree is too high, the crystals in the polyvinyl alcohol film are dissolved too easily, resulting in an insufficient amount of crystals in the polyvinyl alcohol film, which reduces the physical strength of the film and makes the film more likely to break.
[0032] Therefore, in order to obtain a polyvinyl alcohol film with both a stable intermolecular structure and good physical strength, the areal swelling degree must be controlled within a specific range. Specifically, the areal swelling degree obtained by immersing the film in a 4 wt% boric acid aqueous solution at 55°C for 1 minute is 17.0 to 38.0%, and is within a range between any two of the following values, for example, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 20.0%, 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%, 25.0%, 25.5%, 26.0%, 26.5%, 27.0%, 27.5%, 28.0%, 28.5%, 29.0%, 30.0%, 31.0%, 32.0%, 33.0%, 34.0%, 35.0%, 36.0%, 37.0%, 38.0%, 39.0%, 40.0%, 41.0%, 42.0%, 43.0%, 44.0%, 45.0%, 46.0%, 47.0%, 48.0%, 49.0%, 50.0%, 51.0%, 52.0%, 53.0%, 54.0%, 55.0%, 56.0%, 57.0%, 58.0%, 59.0%, 60.0%, 61.0%, 62.0%, 63.0%, 64.0%, 65.0%, 66.0%, 67.0%, 68.0%, 69.0%, 70.0%, 71.0%, 72. %, 27.0%, 27.5%, 28.0%, 28.5%, 29.0%, 29.5%, 30.0%, 30.5%, 31.0%, 31.5%, 32.0%, 32.5%, 33.0%, 33.5%, 34.0%, 34.5%, 35.0%, 35.5%, 36.0%, 36.5%, 37.0%, 37.5%, or 38.0%, and preferably, the areal swelling degree of the polyvinyl alcohol film is 17.5 to 35.0% or 35%.
[0033] The "elastic modulus" mentioned in this specification is a physical property used to analyze the relationship between stress and strain in material mechanics, and is the ratio of stress to strain. The elastic modulus obtained when the stress applied to the material is a normal force is represented by E. The "storage modulus (E')" is the component that the material absorbs and converts the applied energy and stores it inside the material, and is usually used to recover deformation and maintain the original appearance of the material, and is related to the elastic properties of the material and can also reflect the rigidity of the material. From the molecular point of view, the larger the storage modulus (E'), the stronger the intermolecular force.
[0034] The "temperature at which the inflection point of the storage modulus (E') in the range of 30°C to 55°C in water (hereinafter referred to as the E' inflection point temperature)" described in this specification is obtained by immersing a polyvinyl alcohol film in water and measuring the change in E' of the polyvinyl alcohol film by a temperature increase method. After a large amount of water is absorbed into the film, the molecular chains of polyvinyl alcohol swell and separate, and the entanglement between the molecular chains decreases. At this time, the response of the storage modulus (E') is more greatly affected by the crystallization in the film and the responsiveness becomes greater, so the analysis of the storage modulus (E') of polyvinyl alcohol immersed in water can be used to evaluate the change in the crystallinity in the film at different temperatures. Furthermore, analysis of a polyvinyl alcohol film in water showed that the change curve of the storage modulus (E') as a function of temperature had the characteristics shown in Figure 1, where the change curve between 30°C and 55°C has two different slopes, the tangent intersection of the two slopes is the E' inflection point, and the corresponding temperature is the E' inflection point temperature (the point indicated by the arrow in Figure 1).
[0035] The inventors have found that the physical meaning represented by the E' inflection point temperature includes the temperature at which the crystals in the polyvinyl alcohol film begin to dissolve in large quantities, and that the higher the E' inflection point temperature, the larger the average crystal grains in the film, and therefore the larger the crystal dissolution occurs only at relatively high temperatures. Without being bound by any particular theory, it is believed that if the crystal grain size is controlled within an appropriate range, the polyvinyl alcohol film has an optimal crystal dissolution amount and region for crosslinking with boric acid, and the optical film (such as a polarizing film) made from the polyvinyl alcohol film has the effect of being less likely to decrease in polarization even when used at high temperatures for a long period of time.
[0036] Therefore, in order to obtain the above-mentioned effects, it is necessary to control the E' inflection point temperature within a specific range. Specifically, the temperature at which the inflection point of the storage modulus (E') of the polyvinyl alcohol film of the present invention in water in the range of 30°C to 55°C (the temperature range of the initial stretching in the production process of the polarizing film) is 37 to 40°C, for example, 37°C, 37.1°C, 37.3°C, 37.5°C, 37.7°C, 37.9°C, 38°C, 38.1°C, 38.3°C, 38.5°C, 38.7°C, 38.9°C, 39°C, 39.1°C, 39.3°C, 39.5°C, 39.7°C, 39.9°C or 40°C, but is not limited thereto. Preferably, the E' inflection point temperature of the polyvinyl alcohol film is 37.8 to 38.5°C, and is a value within a range between any two of the following values, for example, 37.8°C, 37.9°C, 38.0°C, 38.1°C, 38.2°C, 38.3°C, 38.4°C, or 38.5°C. If the measurement temperature exceeds 55°C, the crystallization of the polyvinyl alcohol film may completely disappear and the physical properties may change suddenly, so when analyzing the inflection point temperature, the analysis temperature range is set not to exceed 55°C.
[0037] Regarding the method for measuring the E' inflection point temperature, since the polyethylene film absorbs moisture (including moisture in the air) and may affect the state of the crystal morphology, etc., the moisture content of each polyethylene film to be measured can be adjusted to the same by pretreatment before measuring the E' inflection point temperature of the polyethylene film, thereby making the state of each polyethylene film to be measured the same. The moisture content can usually be adjusted to about 8 to 9 wt%, but is not limited thereto in the present specification.
[0038] The "saponification degree" referred to in this specification means a measured value obtained by a test method described in the JIS K 6726 (1994) standard. In one or more embodiments, the saponification degree of the polyvinyl alcohol resin is 95 mol% or more, for example, 95 mol% or more, 95.5 mol% or more, 96 mol% or more, 96.5 mol% or more, 97 mol% or more, 97.5 mol% or more, 98 mol% or more, 98.5 mol% or more, 99 mol% or more, or 99.5 mol% or more. According to one embodiment of the present invention, the saponification degree of the polyvinyl alcohol-based resin of the present invention is greater than 99.90 mol%, for example, greater than 99.90 mol%, greater than 99.92 mol%, greater than 99.94 mol%, greater than 99.96 mol%, or greater than 99.98 mol%. Preferably, the saponification degree of the polyvinyl alcohol-based resin is 99.95 mol% or more, for example, 99.95 mol% or more, 99.97 mol% or more, or 99.99 mol% or more. More preferably, the saponification degree of the polyvinyl alcohol-based resin is 99.97 mol% or more, for example, 99.97 mol% or more, 99.98 mol% or more, or 99.99 mol% or more.
[0039] The "swelling degree in the TD direction (hereinafter referred to as the swelling degree in the TD direction) and the swelling degree in the MD direction (hereinafter referred to as the swelling degree in the MD direction) obtained by immersing a polyvinyl alcohol film in a 4 wt% boric acid solution at 55°C for 1 minute" described in this specification are obtained by calculating the change in length along the TD direction and the MD direction of the polyvinyl alcohol film after immersing the film in a 4 wt% boric acid solution at 55°C for 1 minute. Here, the TD direction is also called the transverse direction, and the MD direction is also called the machine direction. Without being bound by a specific theory, if the swelling degree in the TD direction and the swelling degree in the MD direction of the polyvinyl alcohol film are controlled within a specific range, the shrinkage rate in the TD direction and the MD direction of the optical film can be reduced thereafter, so that the optical film attached to the display can avoid warping of the corners of the optical film when used at high temperatures for a long period of time.
[0040] Therefore, in order to obtain the above-mentioned effects, the swelling degree in the TD direction of the polyvinyl alcohol film of the present invention is 9.0 to 18.0%, and is a value within a range between any two of the following values, for example, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0, 17.5% or 18.0%, and more preferably, the swelling degree in the TD direction of the polyvinyl alcohol film is 9.0 to 16.5%. The swelling degree of the polyvinyl alcohol film in the MD direction is 7.5 to 16.0%, and is a value within a range between any two of the following values, for example, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5% or 16.0%, and more preferably, the swelling degree of the polyvinyl alcohol film in the MD direction is 8.0 to 16.0%.
[0041] In one or more embodiments, the absolute value of the difference between the swelling degree in the TD direction and the swelling degree in the MD direction of the polyvinyl alcohol film is 5% or less, for example, 5% or less, 4.5% or less, 4% or less, 3.5% or less, 3% or less, 2.5% or less, 2% or less, 1.5% or less, 1% or less, or 0.5% or less.
[0042] In one or more embodiments, the ratio of the swelling degree in the TD direction to the swelling degree in the MD direction of the polyvinyl alcohol film is 0.95 to 1.60, and is a value within a range between any two of the following values, for example, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, or 1.60.
[0043] Without being bound by any particular theory, if the absolute value or ratio of the difference between the swelling degree in the TD direction and the swelling degree in the MD direction is too large, peeling may occur between the polarizing film and the protective layer or between the polarizing film and the glass in a display containing the polyvinyl alcohol film produced thereafter, resulting in a problem of deterioration of the display.
[0044] The "average degree of polymerization" described in this specification means a measured value obtained by a test method described in the JIS K 6726 (1994) standard. In one or more embodiments, the average degree of polymerization of the polyvinyl alcohol film is 1500 to 3500, and is a value within a range between any two of the following values, for example, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, or 3500, and preferably the average degree of polymerization of the polyvinyl alcohol film is 2000 to 3500.
[0045] The inventors have found, without being bound by any particular theory, that the above-mentioned areal swelling degree, E' inflection point temperature, swelling degree in the TD direction, and swelling degree in the MD direction can be controlled by adjusting the average polymerization degree of the resin raw materials of the polyvinyl alcohol film, as well as by adjusting the dissolution temperature and time of the raw materials in the production method, the total drying time at a temperature exceeding 50°C, and the molecular orientation of the polyvinyl alcohol polymer in the polyvinyl alcohol film, but are not limited thereto.
[0046] [Method of manufacturing polyvinyl alcohol film] The method for producing a polyvinyl alcohol film of the present invention includes (a) a dissolving step of heating and dissolving a polyvinyl alcohol resin, adjusting the concentration of the polyvinyl alcohol resin to form a polyvinyl alcohol casting solution, (b) a casting step of casting the polyvinyl alcohol casting solution onto a casting drum, peeling it off from the casting drum, and obtaining a preformed film, (c) a heating roller step of contacting the polyvinyl alcohol preformed film with a plurality of heating rollers to obtain a polyvinyl alcohol film semiformed product, (d) an oven step of drying the polyvinyl alcohol film semiformed product in an oven, and (e) a temperature and humidity adjustment step of putting the polyvinyl alcohol film molded product into a temperature and humidity regulator to adjust the temperature and humidity to obtain a polyvinyl alcohol film. Here, in the heating roller and oven steps, the total drying time at a temperature exceeding 50°C is controlled to 10 to 20 minutes.
[0047] [Dissolution process] According to some embodiments, the dissolving step involves increasing the temperature to 130-165°C while stirring the polyvinyl alcohol resin, solvent, plasticizer, etc., dissolving for 1-5 hours, and adjusting the resin to an appropriate concentration to obtain a polyvinyl alcohol casting solution. The appropriate concentration of the resin is about 20wt%-50wt%, for example, 20, 30, 40, or 50wt%. If the resin concentration is too low, the subsequent drying load of the film will be high, and conversely, if the resin concentration is too high, the viscosity will be too high, making film formation difficult.
[0048] In one or more embodiments, the polyvinyl alcohol resin used in the dissolution step is polymerized by a vinyl ester resin monomer to form a polyvinyl alcohol resin with an average degree of polymerization of 1500 to 3500, and then a saponification reaction is carried out to obtain a polyvinyl alcohol resin with a degree of saponification of more than 95%. The average degree of polymerization probably affects the dissolution and elongation of polyvinyl alcohol molecules in water, thereby affecting the crystal particles and crystallinity of the polyvinyl alcohol film molded product. The higher the degree of polymerization, the larger the crystal particles of the polyvinyl alcohol film molded product will be, and the higher the crystallinity will be. However, if the degree of polymerization is too high, the crystal particles will be too large, which will affect the E' inflection point temperature, and if the degree of polymerization is too low, the E' inflection point will be too low, and the mechanical strength of the film will be too low.
[0049] The vinyl ester resin monomer may be vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate, or vinyl octoate, or a combination thereof, but is not limited thereto in the present invention. Preferably, vinyl acetate is used. The vinyl ester resin monomer may be modified by adding an olefin compound or an acrylic ester derivative and copolymerizing it. Here, the olefin compound may be ethylene, propylene, or butene, but is not limited thereto in the present invention. The amount of the olefin compound added may be 2 to 4 mol%, for example, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, or 4 mol%, but is not limited thereto. The acrylate derivative may be acrylic acid, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, or n-butyl acrylate, but is not limited thereto in the present invention.
[0050] In one or more embodiments, the solvent used in the dissolving step is not particularly limited in the present invention, as long as it can dissolve polyvinyl alcohol resin. Examples of the solvent include, but are not limited to, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylenediamine, diethylenetriamine, etc., and the above solvents can be used alone or in combination of two or more. Considering environmental and economical aspects, it is preferable to use water as the solvent in the present invention.
[0051] In one or more embodiments, the "plasticizer" described herein is specifically, but not limited to, glycerin, ethylene glycol, propylene glycol, diethylene glycol, diglycerol, triethylene glycol, tetraethylene glycol, trimethylolpropane, or a combination thereof. In the present invention, glycerin is preferable. In one or more embodiments, the amount of the plasticizer added is 5 to 15 wt% based on the weight of the polyvinyl alcohol resin, specifically, for example, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, and 15 wt%, but not limited thereto. In a preferred embodiment, the amount of the plasticizer added is 10 wt% based on the weight of the polyvinyl alcohol resin.
[0052] In addition to the plasticizer, other additives including, but not limited to, surfactants may be added as necessary in the dissolution step. The surfactants include, but are not limited to, cationic, anionic or nonionic surfactants, and specifically include, but are not limited to, carboxylate types such as potassium laurate, sulfate types such as sodium lauryl sulfate, sulfonate types such as dodecylbenzenesulfonate, alkylphenyl ether types such as polyoxyethylene octylphenyl ether, alcohol phenyl ether types such as polyethylene glycol monooctylphenyl ether, alkyl ester types such as polyethylene glycol monolaurate, alkylamine types such as polyoxyethylene laurylamino ether, alkylamide types such as polyoxyethylene lauramide, polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether, alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide, allyl phenyl ether types such as polyoxyallyl phenyl ether, or sodium lauryl alcohol polyoxyethylene ether sulfate.
[0053] In one or more embodiments, the temperature at which the polyvinyl alcohol-based resin aqueous solution is dissolved is preferably 130 to 165°C, and is a value within a range between any two of the following values, specifically, for example, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C or 165°C. The dissolution temperature probably affects the dissolution of the polyvinyl alcohol resin and the dispersion of the additives. The higher the dissolution temperature, the better the dissolution of the polyvinyl alcohol resin and the dispersion effect of the additives, and the smaller the crystal particles of the polyvinyl alcohol film formed, and the lower the crystallinity. However, if the dissolution temperature is too high, the formed polyvinyl alcohol film may locally turn yellow. Conversely, without being bound by a specific theory, if the dissolution temperature is too low, the dissolution of the polyvinyl alcohol resin and the dispersion effect of the additives are poor, and the crystal particles of the formed polyvinyl alcohol film become relatively large, so that the E' inflection point temperature of the polyvinyl alcohol film becomes too high.
[0054] In one or more embodiments, the time for dissolving the polyvinyl alcohol-based resin aqueous solution is preferably 1 to 5 hours, specifically, for example, 1 hour, 2 hours, 3 hours, 4 hours, or 5 hours, as a value within the range between any two of the following values. The dissolution time probably affects the dissolution of the polyvinyl alcohol resin and the dispersion of the additives. The longer the dissolution time, the better the dissolution of the polyvinyl alcohol resin and the dispersion of the additives, and the smaller the crystal particles of the polyvinyl alcohol film, and the lower the crystallinity. On the other hand, without being bound by a specific theory, if the dissolution time is too short, the dissolution of the polyvinyl alcohol resin and the dispersion effect of the additives are poor, and the crystal particles of the formed polyvinyl alcohol film are relatively large, so that the E' inflection point temperature of the polyvinyl alcohol film becomes too high.
[0055] [Casting process] According to some embodiments, the casting process mainly involves sending the polyvinyl alcohol casting solution to a twin-screw extruder, mixing the solution uniformly again in the extruder, degassing the solution (for example, but not limited to, degassing the solution in a twin-screw extruder), discharging the solution from a T-die lip, and casting the solution onto a rotating high-temperature casting drum (also called a casting drum) or a casting drum such as an endless belt as a support to obtain a polyvinyl alcohol preformed film. In one or more embodiments, the temperature of the polyvinyl alcohol casting solution during transportation is preferably at least 90°C or higher (for example, but not limited to, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, or 99°C). The polyvinyl alcohol casting solution after being mixed uniformly again in the extruder and degassed must also be controlled to at least 90°C or higher (for example, but not limited to, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, or 98°C).
[0056] In one or more embodiments, when the polyvinyl alcohol casting solution is cast onto a rotating high-temperature casting drum, the temperature of the casting drum is preferably 85 to 95° C., and the residence time of the polyvinyl alcohol on the casting drum is preferably 0.6 to 1.2 minutes.
[0057] [Heating roller process] According to some embodiments, the heating roller process mainly involves contacting and drying the upper and lower surfaces of the polyvinyl alcohol preformed film peeled off from the casting drum with multiple heating rollers, and then obtaining a polyvinyl alcohol film semi-formed product. The temperature of the multiple heating rollers (e.g., 13 to 19 heating rollers) gradually decreases from high to low, with the first heating roller being the roller with the highest temperature among all the heating rollers (e.g., 90 to 99°C, but not limited thereto, specifically, for example, 90, 91, 92, 93, 94, 95, 96, 97, 98, or 99°C, but not limited thereto), and the temperature of the last heating roller being the lowest among all the heating rollers (e.g., 25 to 40°C, but not limited thereto, specifically, for example, 25, 30, 35, or 40°C, but not limited thereto).
[0058] [Oven process] According to some embodiments, the oven process is mainly to obtain a polyvinyl alcohol film molded product by drying the upper and lower surfaces of the polyvinyl alcohol film semi-molded product peeled off from the heating roller in an oven (for example, but not limited to, drying with hot air or infrared rays). In one or more embodiments, the oven is preferably a floating oven, and the temperature is controlled in the range of 100°C to 120°C (for example, 100°C, 105°C, 110°C, 115°C, or 120°C, preferably 110°C).
[0059] In one or more embodiments, in the heating roller process and the oven process, the total drying time at a temperature exceeding 50°C is 10 to 20 minutes (for example, 10 minutes, 15 minutes, or 20 minutes). The total drying time at a temperature exceeding 50°C probably affects the areal swelling degree, swelling degree in the TD direction, swelling degree in the MD direction, and E' inflection point temperature of the polyvinyl alcohol film. Without being bound by any theory, it is likely that when the water content is 2wt%, the glass transition temperature of the polyvinyl alcohol film molded product is 40 to 50°C, so when the drying temperature exceeds 50°C, the polymer chains can move freely within a narrow range. Therefore, the longer the total drying time, the larger the crystal particles become and the higher the crystallinity becomes, and conversely, the shorter the total drying time, the smaller the crystal particles become and the lower the crystallinity becomes, which affects the swelling degree and E' inflection point temperature of the polyvinyl alcohol film.
[0060] [Temperature and humidity adjustment process] According to a preferred embodiment of the present invention, the polyvinyl alcohol film product can be further placed in a temperature and humidity regulator to adjust the temperature and humidity after the above steps.
[0061] In one or more embodiments, the temperature of the temperature and humidity regulator is in the range of 35 to 45°C, specifically, a value within a range between any two of the following values, for example, 35°C, 40°C, or 45°C, and preferably 45°C. In one or more embodiments, the relative humidity of the temperature and humidity regulator is in the range of 40 to 60%, specifically, a value within a range between any two of the following values, for example, 40%, 45%, 50%, 55%, or 60%, and preferably 50%. In one or more embodiments, the time for which the polyvinyl alcohol film is left in the temperature and humidity regulator is, for example, 20 minutes, 25 minutes, 30 minutes, 35 minutes, or 40 minutes, and preferably in the range of 20 to 40 minutes. In one or more embodiments, for example, the polyvinyl alcohol film is left in a temperature and humidity regulator at a temperature of 45°C and a relative humidity of 50% for 30 minutes.
[0062] According to a preferred embodiment of the present invention, in the oven process, both sides of the film are further clamped and a tensile force is separately applied in the TD direction to maintain the film dimensions in the TD direction, thereby adjusting the molecular orientation of the film. Since polyvinyl alcohol films are generally stretched in the MD direction, and polyvinyl alcohol polymers tend to be oriented along the MD direction, the difference in swelling degree between the two directions can be reduced by applying a force separately to the film in the TD direction and then maintaining a balance in the orientation of the polyvinyl alcohol polymer.
[0063] [Optical film] Another object of the present invention is to provide an optical film made from said polyvinyl alcohol film. The "optical film" mentioned in this specification can be a polarizing film, a retardation film, a viewing angle widening film, a brightness enhancing film, etc., and is particularly a polarizing film.
[0064] The "degree of polarization" referred to in this specification means a measured value obtained by the test method described in the standard JIS Z 8722. In one or more embodiments, the degree of polarization of the polarizing film of the present invention is 99.99% or more, for example, 99.990% or more, 99.992% or more, 99.994% or more, 99.996% or more, or 99.998% or more.
[0065] In one or more embodiments, when the polarizing film is heat-treated at 80° C. for 500 hours, the decrease in polarization degree is 0.01% or less, for example, 0.010% or less, 0.009% or less, 0.008% or less, 0.007% or less, 0.006% or less, or 0.005% or less.
[0066] In one or more embodiments, the polarizing film is heat-treated at 80°C for 500 hours, and the area shrinkage rate is 2% or less, for example, 2% or less, 1.9% or less, 1.8% or less, 1.7% or less, 1.6% or less, 1.5% or less, or 1.4% or less.
[0067] In one or more embodiments, the polarizing film is heat-treated at 80°C for 500 hours, and the shrinkage percentages in the TD and MD are both 1% or less, for example, both 1% or less, both 0.95% or less, both 0.90% or less, both 0.85% or less, both 0.80% or less, or both 0.75% or less.
[0068] [Method of manufacturing optical film] According to some embodiments, the "method of manufacturing an optical film" of the present invention refers to a method of manufacturing a polarizing film, and further comprises manufacturing a polyvinyl alcohol film into a polarizing film. The method of manufacturing the polarizing film includes a dyeing step of adsorbing iodide ions, a boric acid treatment step, and a water washing step, and a stretching step of uniaxial stretching can be performed in the boric acid treatment step or a step before this. Preferably, a swelling step of swelling the polyvinyl alcohol film with water can be provided before the dyeing step. Note that a final drying step is usually provided after the water washing step.
[0069] In the swelling step, the polyvinyl alcohol film is immersed in a treatment bath (e.g., pure water) at a temperature of 30°C to 55°C, for example, to wash the film surface and perform a swelling treatment. The swelling treatment time is usually 5 to 300 seconds, preferably 20 to 240 seconds. According to some embodiments, a plurality of guide rollers are arranged in a swelling tank containing the treatment bath in order to transport the polyvinyl alcohol film. Next, the polyvinyl alcohol film is stretched in the MD direction to 1.05 to 2.5 times its original length, and then a dyeing step is performed.
[0070] In the dyeing process, the polyvinyl alcohol film that has been through the swelling process is immersed in a dyeing tank containing a dye bath. The dyeing conditions can be determined within a range in which iodine is adsorbed onto the polyvinyl alcohol film and does not cause defects such as extreme dissolution or devitrification of the film. The dye bath in the dyeing process can be, for example, an aqueous solution containing iodine and potassium iodide, and the concentration of iodine in the dye bath is preferably 0.01 to 0.5 wt%, and the concentration of potassium iodide is preferably 0.01 to 10 wt%. Specific examples include, but are not limited to, an aqueous solution containing 0.037 wt% iodine and 1.85 wt% potassium iodide. In place of potassium iodide, other iodides such as zinc iodide may be used, or other iodides may be used in addition to potassium iodide. The temperature of the dye bath is usually 20 to 40° C., for example, 20, 30 or 40° C., and the time of the dyeing treatment (dyeing time) is usually 10 to 600 seconds, preferably 30 to 200 seconds. Next, the polyvinyl alcohol film is stretched in the machine direction to 2 to 4 times its original length, and then a boric acid treatment and a stretching step are carried out.
[0071] In the boric acid treatment and stretching process, the polyvinyl alcohol film dyed with iodine is treated with a boric acid-containing aqueous solution to crosslink, and the adsorbed iodine is fixed to the resin. The process is usually carried out by immersing the polyvinyl alcohol film that has been subjected to the dyeing process in a fixing tank containing a boric acid-containing treatment bath. The boric acid treatment bath preferably contains iodide in addition to boric acid, and examples of the iodide used here include potassium iodide or zinc iodide, and examples of the iodide include aqueous solutions containing boric acid and potassium iodide at a concentration of 5.5 wt% each. In addition, compounds other than iodide, such as zinc chloride, cobalt chloride, zirconium chloride, sodium thiosulfate, potassium sulfite, sodium sulfite, potassium sulfate, sodium sulfate, etc., may also be present in the boric acid treatment bath. The boric acid treatment and stretching process are usually carried out at a temperature of 50 to 70°C, preferably at a temperature of 55°C, and the processing time is usually 10 to 600 seconds, preferably 20 to 300 seconds, more preferably 20 to 100 seconds. Next, the polyvinyl alcohol film is stretched in the machine direction to 3 times or more of the original length, and the subsequent process is carried out. The upper limit of the stretching ratio is not particularly limited, but is preferably less than 8 times, for example. The stretching ratio includes, but is not limited to, 3.3 times or more, for example, 3.3 to 8.0 times, more preferably 3.5 to 6.0 times, and particularly preferably 4.0 to 5.5 times.
[0072] After the polyvinyl alcohol film is subjected to the above process and the subsequent washing and drying processes, a polarizing film is formed. In the washing and drying processes, the iodine solution and boric acid remaining on the film surface are washed with water or an aqueous solution containing iodide (for example, but not limited to, washing with an aqueous potassium iodide solution having a concentration of 5.5 wt%). Next, after a drying process (for example, but not limited to, drying in an oven at a temperature of 60° C. for 5 minutes), a polarizing film is formed. Furthermore, a protective layer can be formed on at least one surface of the polarizing film to manufacture a finished polarizing film (also called a polarizer). In detail, the protective layer has a function such as preventing wear of the surface of the polarizing film, and is preferably a component containing a transparent resin. According to different embodiments, the protective layer is provided on only one surface of the polarizing film, but it is preferable that the protective layer is formed on both surfaces of the polarizing film. The protective layer can be a protective film made of a transparent resin material. The transparent resin may be an acrylic resin such as a methyl methacrylate resin, an olefin resin, a polyvinyl chloride resin, a cellulose resin, a styrene resin, an acrylonitrile-butadiene-styrene copolymer resin, an acrylonitrile-styrene copolymer resin, a polyvinyl acetate resin, a polyvinylidene chloride resin, a polyamide resin, a polyacetal resin, a polycarbonate resin, a modified polyphenylene ether resin, a polyester resin (such as a polybutylene terephthalate resin or a polyethylene terephthalate resin), a polysulfone resin, a polyethersulfone resin, a polyarylate resin, a polyimideimide resin, a polyimide resin, an epoxy resin, an oxetane resin, or the like, and a cellulose resin such as cellulose triacetate (TAC) is preferred. EXAMPLES
[0073] The present invention will be described in detail below with reference to specific examples. However, it should be understood that these specific examples are intended to aid in the understanding of the present invention and are not intended to limit the scope of the present invention in any way.
[0074] 1. Preparation of Polyvinyl Alcohol Film Here, the present invention provides a non-limiting method for preparing polyvinyl alcohol films. The polyvinyl alcohol films of the non-limiting examples (Examples 1-12) and the polyvinyl alcohol films of the comparative examples (Comparative Examples 1-5) are prepared in a manner similar to that disclosed below.
[0075] The following are the main steps common to the production of polyvinyl alcohol films in this embodiment and the comparative example, and the following Table 1 details the differences in one or more process parameters between this embodiment and the comparative example.
[0076] [Dissolution process] 1800 kg of polyvinyl alcohol resin with an average degree of polymerization of 1500-3500 (see Table 1) and a degree of saponification of 99.95 mol%, 4000 kg of water, and 180 kg of plasticizer glycerol were added to a dissolution barrel, and the dissolution temperature was raised to 130-165°C (see Table 1) while stirring, and the dissolution time was controlled to 1-5 hours (see Table 1). After uniform dissolution, water was added to adjust the resin concentration to 30 wt%, and a polyvinyl alcohol casting solution was obtained. The polyvinyl alcohol resin in the examples and comparative examples is a polyvinyl alcohol resin that is polymerized with vinyl acetate and is not modified (i.e., does not contain other comonomers). The specific average degree of polymerization, dissolution temperature, and dissolution time of the polyvinyl alcohol resin are shown in Table 1.
[0077] [Casting process] The polyvinyl alcohol casting solution is transported to a twin screw extruder, where it is mixed uniformly again and degassed. The temperature of the casting solution is controlled to 98°C, and then the casting solution is discharged from a T-die lip and cast onto a rotating high-temperature casting drum, where it is dried and formed into a film, forming a preformed film.
[0078] [Heating roller process] After the polyvinyl alcohol preformed film is peeled off from the casting drum, the top and bottom surfaces of the film are contact-dried with 13 heating rollers. The first heating roller is the hottest roller (95°C) of all the heating rollers, and the temperature of the subsequent heating rollers gradually decreases from high to low, until the temperature of the 13th heating roller decreases to 30°C.
[0079] [Oven process] The film is dried in a floating oven, and both the top and bottom surfaces of the film are dried with hot air and infrared rays to produce a polyvinyl alcohol film product. In another example, when the film is dried in a floating oven, clamps are further placed on both sides of the film to apply a tensile force in the TD direction to maintain the film dimensions in the TD direction.
[0080] Here, in the above casting, hot roller and oven steps, the total drying time at a temperature above 50° C. is controlled (the specific duration is shown in Table 1).
[0081] [Temperature and humidity adjustment process] Thereafter, the polyvinyl alcohol film molded product was placed in a temperature and humidity controller at a temperature of 45° C. and a relative humidity of 50% for 30 minutes to obtain a polyvinyl alcohol film.
[0082] [Table 1]
[0083] 2. Preparation of Polarizing Films Here, the present invention provides a non-limiting method for preparing an optical film from a polyvinyl alcohol film, in particular a non-limiting method for preparing a polarizing film. According to the method disclosed below, the polyvinyl alcohol films of the non-limiting examples (Examples 1-12) and the polyvinyl alcohol films of the comparative examples (Comparative Examples 1-5) are prepared into corresponding polarizers.
[0084] The main steps common to the preparation of the polarizing film in the examples and comparative examples of the present invention are as follows: After unwinding the polyvinyl alcohol film, it is put into a swelling tank filled with pure water at 30°C to wash and swell the film surface, and the polyvinyl alcohol film is stretched in the machine direction to 1.2 times its original length, and then the temperature is controlled to 30°C and the film is placed in a dyeing tank containing an aqueous solution of 0.037 wt% iodine and 1.85 wt% potassium iodide to be dyed and stretched in the machine direction to 3.4 times its original length. After dyeing, the temperature is controlled to 55°C and the film is placed in a stretching tank containing an aqueous solution of boric acid and potassium iodide at 5.5 wt% each, and the polyvinyl alcohol film is stretched in the machine direction to 6 times its original length, and the iodine water and boric acid remaining on the film surface are washed with an aqueous solution containing 5.5 wt% potassium iodide. Next, the film was dried in an oven at 60° C. for 5 minutes, and cellulose triacetate protective films were attached to the upper and lower surfaces and dried to produce a polarizing film.
[0085] 3.Analysis method Here, the present invention provides methods for analyzing and testing the polyvinyl alcohol films of Examples 1 to 12 and Comparative Examples 1 to 5 above.
[0086] <Saponification degree> The method for measuring the saponification degree in the present invention is the test method described in JIS K 6726 (1994) standard.
[0087] <Average degree of polymerization> The method for measuring the degree of polymerization in the present invention is the test method described in JIS K 6726 (1994).
[0088] <Swelling degree> 1. Test conditions: Cut the polyvinyl alcohol film into a square sample with a size of 10 cm in the MD direction × 10 cm in the TD direction. Clamp the edge of the sample together with the glass using a long-tail clip, immerse it in a 4 wt% boric acid solution at 55 °C for 1 minute to swell it. After the swelling is complete, take out the sample and the glass, remove the long-tail clip, flatten the swollen sample, and measure the lengths in the MD direction and TD direction of the swollen sample with a vernier caliper respectively.
[0089] 2. The calculation formulas for the degree of swelling in each direction (MD direction and TD direction) are expressed as follows.
[0090]
Number
[0091] 3. The calculation formula for the area swelling degree is expressed as follows.
[0092]
Number
[0093] <E’ inflection point temperature> 1. Equipment and its brand: DMA 850 of TA Instruments 2. Sample preparation method: A polyvinyl alcohol film is cut into a long strip of 5 cm in the machine direction (MD) and 5 mm in the transverse direction (TD), and the moisture content of the polyvinyl alcohol film is adjusted to 8-9 wt% before being set in the machine to make the state of the polyvinyl alcohol film consistent. Next, referring to FIG. 2, one end of the polyvinyl alcohol film 2 is fixed with a dovetail clip 3 weighing about 1.11 g, and the other end is inserted into the immersion stretching jig 1, and a part of the polyvinyl alcohol film 2 is placed between the upper fixed shaft 1a and the lower fixed shaft 1b, and the bottom end 3a of the dovetail clip 3 is 1 cm away from the immersion stretching jig 1 (distance a shown in FIG. 2), leaving a space between the upper end 2a of the polyvinyl alcohol film 2 and the upper end of the immersion stretching jig 1. Next, the upper fixed shaft 1a is tightened to fix the polyvinyl alcohol film 2. 3, the entire immersion stretching jig 1, the polyvinyl alcohol film 2 held therein, and the dovetail clip 3 are placed vertically in a 100 mL beaker 4 filled with pure water so that the liquid level of the beaker is located at the upper fixed shaft 1a, the beaker 4 is temperature-controlled in a thermostatic water bath (not shown) at 30° C., and a load (weight of the dovetail clip 3) is applied to the polyvinyl alcohol film 2 to cause it to swell for 20 minutes. Finally, referring to FIG. 4, the immersion stretching jig 1 is removed from the beaker 4 and held vertically, and the polyvinyl alcohol film 2 is stretched by the weight of the dovetail clip 3. After confirming that the polyvinyl alcohol film 2 is in the center, the lower fixed shaft 1b of the immersion stretching jig 1 is tightened, and the excess polyvinyl alcohol film 2c (the mesh-like portion in FIG. 4) is cut off, and the sample is the polyvinyl alcohol film 2b clamped to the immersion stretching jig 1 and subjected to the load and swelling.
[0094] 3. Test conditions: When the above sample is still fixed in the immersion and stretching fixture, select the vibration heating mode, place the sample and the immersion stretching fixture 1 holding the sample together in an immersion bath filled with deionized water, set the frequency to 1Hz, the amplitude to 200μm, the force track to 200%, set the temperature to measure from 30℃ to 65℃, stretch the film with a static force of 0.15N before analysis, then start analyzing with a heating rate of 1℃ / min, and draw the storage modulus (E') vs. temperature change curve. Here, the detection end of the thermocouple is placed at a height of 5mm from the bottom of the water bath.
[0095] 4. Data processing: Convert the storage modulus (E') coordinate axis into a linear coordinate axis, use the onset analysis built into the software provided with the instrument, and set the onset analysis temperature range to 30-45°C. The software will automatically input the inflection point temperature.
[0096] 4. Evaluation method and results Here, the present invention provides the evaluation methods of the polyvinyl alcohol film and the polarizing film in the examples and comparative examples, and the results of the correspondence with the above-mentioned analysis contents.
[0097] <Evaluation of the degree of polarization> Test conditions: The polarizing film was cut into two square samples measuring 4 cm in MD × 4 cm in TD. The two polarizing film samples were then stacked parallel to the MD (i.e., flow direction). The light transmittance (H11) was measured using a spectrophotometer when irradiated with light of a wavelength of 700 nm. The two polarizing film samples were then stacked perpendicular to the MD. The light transmittance (H1) was measured when irradiated with light of a wavelength of 700 nm. This was calculated using the polarization formula below.
[0098]
number
[0099] <Evaluation of Decreased Polarization Degree> Test conditions: The polarizing film is placed in an oven at 80°C and heat-treated for 500 hours, after which the polarization degree is measured again and the decrease in polarization degree is calculated using the following formula.
[0100]
number
[0101] Furthermore, the areal swelling degree and E' inflection point temperature of the polyvinyl alcohol films of Examples 1 to 12 and Comparative Examples 1 to 5 of the present invention are shown in Table 2 together with the evaluation of the polarization degree and the evaluation of the polarization degree decrease value of the corresponding polarizing films.
[0102] [Table 2]
[0103] As can be seen from Table 2, in the analysis of the area swelling degree and E' inflection point temperature of the polyvinyl alcohol film samples of Examples 1 to 12, the measured area swelling degrees are all 17.0 to 38.0%, the E' inflection point temperatures are all 37 to 40°C, the polarization degrees of the polarizing films made of these polyvinyl alcohol films all exceed 99.99%, and the polarization degree reduction values are all 0.010% or less, so that excellent evaluations of the polarization degree and the polarization degree reduction value are obtained. On the other hand, in the analysis of the area swelling degree and E' inflection point temperature of the polyvinyl alcohol film samples of Comparative Examples 1 to 5, the measured area swelling degree and E' inflection point temperature cannot be simultaneously within the above specific range, and the polarization degree reduction values of the polarizing films made of these polyvinyl alcohol films all exceed 0.010%, so that ideal results cannot be obtained in both the evaluation of the polarization degree and the evaluation of the polarization degree reduction value. In light of this, by simply controlling the polyvinyl alcohol film so that it has an areal swelling degree of 17.0 to 38.0% when immersed in a 4 wt% boric acid solution at 55°C for 1 minute, and the temperature at which the inflection point of the storage modulus (E') of the polyvinyl alcohol film in water at 30°C to 55°C is 37°C to 40°C, the polarized film produced not only has a good degree of polarization, but also improves the deterioration of the degree of polarization.
[0104] <Evaluation of shrinkage rate> 1. Test conditions: The polarizing film is cut into a square sample of 10 cm in the MD x 10 cm in the TD, and heat-treated in an oven at 80°C for 500 hours. After removing it and returning it to room temperature, the lengths in the MD and TD are measured with a vernier caliper, and the shrinkage rate in the MD, TD and area shrinkage rates are calculated using the following shrinkage rate formula.
[0105] 2. The shrinkage rate formula for each direction (MD and TD) is expressed as follows:
[0106]
number
[0107] 3. The area shrinkage rate formula is expressed as follows:
[0108]
number
[0109] Furthermore, the swelling degree in the TD direction, the swelling degree in the MD direction, the difference in swelling degree, and the swelling degree ratio (TD / MD) of the polyvinyl alcohol films of Examples 1 to 12 of the present invention and Comparative Examples 1 to 5 are shown in Table 3 together with the area shrinkage rate, the shrinkage rate in the TD direction, and the shrinkage rate in the MD direction of the corresponding polarizing films.
[0110] [Table 3]
[0111] As can be seen from Table 3, the areal swelling degree, TD swelling degree and MD swelling degree of the polyvinyl alcohol films of Examples 1 to 12 are in the ranges of 17.0 to 38.0%, 9.0 to 18.0% and 7.5 to 18.0%, respectively, so that the manufactured polarizing films have the characteristics of an areal shrinkage rate of 2% or less, a TD shrinkage rate of 1% or less and a MD shrinkage rate of 1% or less. Further observation shows that Comparative Example 3 is ideal in terms of the areal shrinkage rate, TD shrinkage rate and MD shrinkage rate of the polarizing film, but the evaluation results of the polarization degree and the polarization degree reduction value are not good, so it is found that it does not have the effect of the present invention, and during the experimental process, it was found that the polyvinyl alcohol film is easily broken during the manufacturing process of the polarizing film. In short, by controlling the areal swelling degree of the polyvinyl alcohol film to 17.0 to 38.0%, the swelling degree in the TD direction to 9.0 to 18.0%, and the swelling degree in the MD direction to 7.5 to 18.0%, the produced polarizing film has a small shrinkage rate and is resistant to deformation even when used for a long period of time in a high temperature environment.
[0112] All ranges provided herein are intended to include each specific range within the stated range, and combinations of subranges between the stated ranges. Also, any range explicitly stated herein includes the endpoints unless otherwise indicated. Thus, the range 1-5 specifically includes 1, 2, 3, 4, and 5, as well as subranges 2-5, 3-5, 2-3, 2-4, 1-4, etc.
[0113] All publications and patents cited in this specification are herein incorporated by reference and for all purposes are specifically and individually indicated to be incorporated by reference into this specification. In the event of a conflict between the specification and a publication or patent document incorporated by reference into this specification, the specification will control. [Explanation of symbols]
[0114] 1. Immersion stretching jig 1a Upper fixed shaft 1b Lower fixed shaft 2 Polyvinyl alcohol film 2a top end 2b Polyvinyl alcohol film after loading and swelling 2c Extra polyvinyl alcohol film 3 Dovetail Clips 3a bottom edge 4 Beaker a Distance
Claims
1. A polyvinyl alcohol film comprising a polyvinyl alcohol resin having a degree of saponification of 95 mol % or more, which has an areal swelling degree of 17.0 to 38.0% obtained by immersion in a 4 wt % aqueous boric acid solution at 55°C for 1 minute, and has an inflection point of a storage modulus (E') in water at a temperature range of 30°C to 55°C of 37 to 40°C.
2. 2. The polyvinyl alcohol film according to claim 1, wherein the area swelling degree is 17.5 to 35.0% and the inflection point temperature is 37.8 to 38.5° C.
3. The polyvinyl alcohol film according to claim 1, wherein the polyvinyl alcohol film obtained by immersing in a 4 wt % boric acid solution at 55° C. for 1 minute has a degree of swelling in a transverse direction (TD) of 9.0 to 18.0% and a degree of swelling in a machine direction (MD) of 7.5 to 18.0%.
4. The polyvinyl alcohol film according to claim 3, wherein the swelling degree in the TD direction is 9.0 to 16.50%, and the swelling degree in the MD direction is 8.0 to 16.0%.
5. The polyvinyl alcohol film according to claim 3 , wherein an absolute value of a difference between the swelling degree in the TD direction and the swelling degree in the MD direction is 5% or less.
6. The polyvinyl alcohol film according to claim 3, wherein the ratio of the swelling degree in the TD direction to the swelling degree in the MD direction is 0.9 to 1.
7.
7. The polyvinyl alcohol film according to claim 5, wherein the ratio of the swelling degree in the TD direction to the swelling degree in the MD direction is 0.95 to 1.
60.
8. The polyvinyl alcohol film according to any one of claims 1 to 7, wherein the polyvinyl alcohol film has an average degree of polymerization of 1,500 to 3,500.
9. The polyvinyl alcohol film according to claim 8, wherein the average polymerization degree of the polyvinyl alcohol film is 2,000 to 3,500.
10. The polyvinyl alcohol film according to any one of claims 1 to 7, wherein the polyvinyl alcohol film has a thickness of 30 to 75 µm.
11. 10. An optical film produced from the polyvinyl alcohol film of claim 1.
12. The optical film according to claim 11, which is a polarizing film.
13. The optical film according to claim 12 , wherein the polarization degree of the polarizing film is 99.99% or more.
14. The optical film according to claim 12 , wherein the polarizing film is heat-treated at 80° C. for 500 hours, and the decrease in the degree of polarization is 0.01% or less.
15. The optical film according to claim 12 , wherein the polarizing film has an area shrinkage rate of 2% or less when heat-treated at 80° C. for 500 hours.
16. 13. The optical film according to claim 12, wherein the polarizing film is heat-treated at 80°C for 500 hours, and the shrinkage rate in both the TD and MD directions is 1% or less.